The public-private sector wage gap in Latvia - Karlis Vilerts (Baltic Journal of Economics, 2018)
This study investigates the public-private sector wage gap in Latvia using microdata from the labour force survey. The severity of public sector wage cuts employed as a response to the economic crisis and subsequent recovery provides a test bed to analyse whether and how the public-private sector wage gap has adjusted after consolidation-driven wage cuts. Findings reveal that the observed wage gap is slightly in favour of the public sector; however, once differences in individual characteristics and selection effects are considered, results point to a private sector wage premium. Findings also suggest that the private sector wage premium has increased since the pre-crisis period. A significant private sector wage premium raises doubts on whether a system that is reliant on discretionary fiscal measures is efficient enough in eliminating unwarranted differences in wage. In particular, whether a re-adjustment process of public sector wages works after consolidation-driven wage cuts.
Keywords: J31; J33; J88; 330; Double sample selection; Oaxaca-Ransom decomposition; public sector wages; public-private sector wage gap